Proximal Tibial Epiphysiodesis in a Growing Dog - Mesquita, Luciane dos Reis [UNESP]; Lopes Muzzi, Leonardo Augusto; Giannico, Amalia Turner; Lazaro Muzzi, Ruthnea Aparecida; Monteiro, Juliana Fonseca; Brienza, Paula Desjardins (Univ Fed Rio Grande Do Sul, 2016)
Background: It is believed that the inclined tibial plateau angle to be a major cause of cranial cruciate ligament (CCL) rupture, and the treatment of this disease is the tibial plateau leveling for decrease the cranial tibial thrust. However, there are breeds predisposed to rupture of the cranial cruciate ligament and in this patterns breed the tibial plateau is more inclined due to the conformation of the limb. The aim of this communication was to evaluate the effectiveness of the locking screw and cauterizing the growth plate of the tibial plateau as a preventive method of cranial cruciate ligament rupture. Case: In a young dog, one stifle joint randomly chosen for placing a screw in order to block the tibial plateau growth line. There was placed a 3.5 mm x 20 mm cancellous bone screw in the dorsocranial surface of the tibial plateau of the left hindlimb. Two months after the first surgical intervention, the contralateral limb was cauterized in the tibial plateau growth line. Electrocauterization was performed with a spatula electrode set at 60 watts, performing ablation on the cranial third of the tibial plateau physis with access to the medial and lateral surfaces of the proximal tibia. The electrode was placed against the physis for 10 seconds at each site. Both members were followed radiographically to measure the tibial plateau angle and observed the angle reduction. After 30 and 60 days post-surgery, the tibial plateau angle in left hindlimb decreased to 11 degrees and -4 degrees, respectively. However, the decrease plateau tibial angle was intense and severe and the screw was removed of the bone. However, even with the proximal tibial physis still open, withdrawing the screw did not alter the tibial plateau angle, which remained at -4 degrees until the animal reached adulthood. The right left hindlimb was used as a control until the dog was 6 months old, when the tibial plateau angle exhibited a 26 degrees. With the electrocauterization technique the tibial plateau angle decreased to 18 degrees and 16 degrees at 30 and 60 days after surgery, respectively, remaining at this last value until the animal completed its growth. Discussion: In the animals with cranial cruciate ligament rupture is indicate same surgical procedures like tibial plateau leveling osteotomy. In these cases, the recommended tibial plateau angle is aproximattely 5 degrees. This study sought to block the line of growth of the tibial plateau to be reached an angle of approximately 5 degrees. Epiphysiodesis technique with screw was already described for treating CCL rupture in young dogs, and the tibial plateau slope was reduced in all dogs studied. The surgical technique used was effective in blocking the physis; however, we observed that the tibial plateau slope was excessively modified and the screw was removed. This fact is explained by the dog's immaturity, since the plateau leveling occurs more intensively in very young dogs. In epiphysiodesis using the electrocauterization technique, the same surgical principle of juvenile pubic symphysiodesis for treating coxofemoral dysplasia was used. However, in the current pilot study, it was unable to achieve the desired tibial plateau slope with this technique, possibly due to performing the procedure at an age in which the proximal tibial physis would have limited functional capacity. In this study, there was a reduction in the angle of the tibial plateau in both the techniques. However, further studies should be conducted to in order to confirm the actual effectiveness of both techniques described in this report.
Keywords: cranial cruciate ligament; locking screw; electrocauterization; stifle joint